Techno-economic viability assessment of hybrid briquettes as an alternative domestic cooking fuel for rural communities in Nigeria - Yusuf, Kpalo Sunday (2021)
Growing global demand and utilization of fossil fuels has not only elevated wealth creation, but also increased adverse impacts of climate change from greenhouse gases (GHGs) emissions which endangered public health. In most developing countries including Nigeria, biomass wastes, which include but are not limited to agricultural residues, are produced in large quantities annually. They are either inefficiently used or disposed of indiscriminately, which threatens the environment. However, there is a way to deal with this situation which is by converting these biomass wastes, through densification, into high-density and energy-efficient briquettes. Densification of biomass into briquettes presents a renewable energy option as an alternative to fossil fuels. This dissertation reports the findings of technical and economic viability assessment of hybrid briquettes developed from a blend of corncobs (CC) and oil palm trunk bark (OPTB) under a low-pressure densification technique. The raw materials were chopped into small pieces and then sun-dried to reduce the moisture content. A grinding machine was used to grind the dried raw materials further and then sieved to obtain the desired particle size The individual materials (corncobs and OPTB) and mixed materials (blend of both) were measured into 1000 g portions and wastepaper pulp (100 g) was added to each mixture as a binder. A total of five different mixtures with distinct identities (namely CC, MIX 1, MIX 2, MIX 3, and OPTB) were formulated according to the quantities of corncobs to OPTB. Briquettes were produced using a manually operated 20- compaction pressure. The quality of the briquettes was determined in terms of physical, mechanical and thermal properties while the performance of the briquettes in a cooking application was determined by a water boiling test. Additionally, the economic feasibility of the hybrid briquette production from a household point of view was determined by a financial model using specific cost-benefit analysis tool. The study revealed that the physical properties of hybrid briquettes ranged from 9.24 10.00% moisture content, 0.38 0.40 g/cm3 density, and 87.60% 92.00% water resistance. Mechanical strength was 98.28% 99.08% shatter index and 18.47 21.75 Mpa compressive strength, while calorific values ranged from 16.54 16.91 MJ/kg. Results also showed that the volatile matter, ash content and calorific value increased with the increase in OPTB in the ratios while the fixed carbon decreased. Water boiling test results showed that hybrid briquettes (MIX 2 and MIX 3) were similar in values based on time taken to ignite briquettes and boil 1 L of water (17.54 min and 17.13 min), fuel burning rate (0.69 kg/h and 0.70 kg/h) and specific fuel consumption (0.16 kg/liter and 0.15 kg/liter). However, MIX 2 performed better in terms of thermal fuel efficiency (17.25%) and produced less quantity of ash during combustion and thus, considered the optimum combination and was chosen for economic evaluation. CO2 emission of all briquettes ranged from 241-281 gCO2e. Economic evaluation of hybrid briquettes showed that it took a minimum of $0.16 to produce 1 kg of hybrid briquettes. On the assumption that it can sell for $0.26 per kg, an annual revenue of $3,637.69 and a net profit of $1,438.69 will be derived. Furthermore, economic feasibility indicators showed that net present value (NPV) was $6,755.91, payback period (PBP) was 2.40 years, internal rate of return (IRR) was 48.8% and benefit cost ratio (BCR) was 1.43. An accounting profit can be achieved as long as briquette sales are above the break-even point of 7,329.8 kg. Sensitivity analysis showed that the risk of a significant reduction in NPV was from operation and maintenance cost, and lower briquett save about 25% from their per-capita expenditure on fuelwood when briquettes are utilized. Overall, it can be inferred that developing briquettes from corncobs and OPTB was technically and economically feasible. The hybrid briquettes are environmentally friendly, cost effective and affordable compared to fuelwood and fossil fuel as alternatives for domestic cooking purposes. They can complement domestic cooking fuels like firewood, charcoal and kerosene, thus decreasing the high demand for such fuels. The addition of briquettes to the energy mix will help to diversify the sources of energy in Nigeria and therefore help to improve the energy security in line with the Adopting briquetting technology will increase access to clean and affordable energy in line with the 7th Development Goals.